If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -2) = (x + -4) + -28 Reorder the terms: 6(-2 + x) = (x + -4) + -28 (-2 * 6 + x * 6) = (x + -4) + -28 (-12 + 6x) = (x + -4) + -28 Reorder the terms: -12 + 6x = (-4 + x) + -28 Remove parenthesis around (-4 + x) -12 + 6x = -4 + x + -28 Reorder the terms: -12 + 6x = -4 + -28 + x Combine like terms: -4 + -28 = -32 -12 + 6x = -32 + x Solving -12 + 6x = -32 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -12 + 6x + -1x = -32 + x + -1x Combine like terms: 6x + -1x = 5x -12 + 5x = -32 + x + -1x Combine like terms: x + -1x = 0 -12 + 5x = -32 + 0 -12 + 5x = -32 Add '12' to each side of the equation. -12 + 12 + 5x = -32 + 12 Combine like terms: -12 + 12 = 0 0 + 5x = -32 + 12 5x = -32 + 12 Combine like terms: -32 + 12 = -20 5x = -20 Divide each side by '5'. x = -4 Simplifying x = -4
| .3x+5=x+3 | | 18x-30= | | .3x+.5=1-0.05x | | f(X)=x^2+6x+1 | | (2x+10)+(6x-4)= | | -7-3y=14 | | 10+25b= | | 8w-6.4=-6.4+5w | | x^2-26x+138=0 | | 1.98g-14=0.89 | | 3(6c-2)=4(10c-7) | | 5x-1=-2 | | 5y-7=-4 | | x^2-x^4=60 | | (.5x+5)-1=-.3(3x-4) | | 3(3u+2v)-3(4u-3v)= | | 4x^2+29x+25=0 | | X^2-Y^2+15X-19Y-6=0 | | 4x^2-25x+19=-2x+4 | | -3x+5-2=x | | 10+10c=3c+3 | | 0=t^2-t-4 | | 3x-5y=-12solvey | | 10+10c=3c+c | | 3n^2-21=2n | | 22.9+3.00= | | 6x-20=3x+13 | | 2r^2-9r=-7 | | -5-t=21 | | 8=10+3x | | 2(2b+10)=12(b-1) | | 15x+8=20+3x |